Penggunaan Media Quizizz untuk Meningkatkan Minat Belajar Peserta Didik Pada Materi Hubungan Pancasila dengan UUD 1945 di SMK Negeri 1 Bancak - Nandisa Velenita; Efi Miftah Faridli; Eko Priyanto (CV. ITTC INDONESIA, 2025)
The purpose of this study is to find out the Use of Quizizz Media to Increase Students' Learning Interest in the Material on the Relationship between Pancasila and the 1945 Constitution at SMK Negeri 1 Bancak. One of the subjects in Indonesia is Pancasila Education. Topics that will be discussed in the Pancasila Education subject include Pancasila as the basis of the Indonesian state, the 1945 Constitution of the Republic of Indonesia as a source of law, and the Unitary State of the Republic of Indonesia which explains how Indonesia became a republic-shaped state. The purpose of this study is to effectively use Quizizz to increase students' interest in learning in the subject of the relationship between Pancasila and the 1945 Constitution at SMK Negeri 1 Bancak. The population in this study is 39 students in class X TKR A at SMK 1 Bancak. This study used a sample of 39 students of class X TKR A at SMK Negeri 1 Bancak. The data collection methods used include observation, interviews and documentation. The data analysis method uses data triangulation which includes data reduction, data presentation and drawing conclusions or data verification. The results of this study show that the Quizizz media at SMK Negeri 1 Bancak can increase students' interest in learning in the material on the relationship between Pancasila and the 1945 Constitution because it presents interactive, fun, and competitive learning. The game feature and live feedback from Quizizz make students more enthusiastic, focused, and active in understanding the material, making the learning process more interesting and less monotonous. Given the importance of technology skills in the modern world, students are advised to continue honing their skills in using other learning technology platforms.